A Study on the Construction of Virtual Simulation Experiments for Basketball Projects (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
Background: Virtual simulation experiments, as a new teaching method and approach, have gradually been introduced into higher education and received recognition from a large number of education professionals. Considering the successful application of virtual simulation experiments in other disciplines, this study aims to employ virtual simulation technology to construct a virtual simulation experiment for basketball projects, with the goal of promoting the application of virtual simulation technology in sports and health education. Methods: The main research methods employed in this study include expert interviews, questionnaire surveys, and software development approaches. A questionnaire survey was conducted among 230 students from six universities, and interviews were conducted with 15 relevant individuals. The demands and requirements of university teachers and students regarding virtual simulation experiments for basketball projects were summarized and refined. The experiment was developed using 3D Studio MAX and Maya as modeling tools. Finally, all aspects of this research were completed through functional validation and application effectiveness evaluation. Results: In the survey stage of needs assessment, a total of 230 questionnaires were collected from six universities. Among them, 63.63% of students claimed to have a relatively good understanding of virtual simulation experiments, 78% of students considered virtual simulation experiments to be of significant importance in teaching, and 84.71% of students regarded this teaching method as relatively relaxed. The development process involved the development of six modules, and after the completion of each module, Unity 3 was used for integration, resulting in the completion of the experiment. Subsequently, functional validation of the virtual simulation was conducted, achieving a 100% pass rate in the testing of various scenarios. An effectiveness evaluation questionnaire was utilized, and the scores from the six dimensions and 20 indicators ranged from a minimum of 3 to a maximum of 5, indicating that university students generally recognized and were satisfied with various aspects of virtual simulation experiments. Conclusion: The construction and application of virtual simulation experiments in China are still in the initial stages, primarily focusing on theoretical research. The virtual simulation experiments were categorized into six sections: basic theoretical learning, technical and tactical application, physical fitness, presentation and competition, rules and refereeing, and observation and evaluation. Various test scenarios were established to assess the interface, performance, and functionality, and both functional validation and application effectiveness evaluation questionnaires yielded positive results. These findings strongly support the assertion that the virtual simulation experiment constructed in this study can serve as an effective supplementary tool for basketball teaching in universities.